The Effectiveness of Problem-Based Learning Model Assisted by GeoGebra Media in Improving Mathematics Problem-Solving Skills of Fifth Grade in Elementary School - Ramadhani, Arifa; Andrijati, Noening (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to gather information about students' problem-solving abilities and explore differences in their skills after using the Problem-Based Learning (PBL) model supported by GeoGebra learning media. The research was conducted because not all students possess strong problem-solving skills and are accustomed to working on problems using these skills. In response to this issue, a quantitative experimental study was carried out with a Quasi-Experimental Design, specifically a Non-Equivalent Control Group Design. The results showed a t value of -3.054 and a significance level (Sig. (2-tailed)) of 0.004. Since this significance value is less than 0.05, it indicates a significant difference between the two groups. The average N-Gain for the control group was 0.187, categorized as low, while the experimental group had an average N-Gain of 0.353, placing it in the medium category. This suggests that there is a significant difference between the group that received GeoGebra-assisted PBL treatment and the group that did not. Overall, students who used the GeoGebra-supported PBL model showed greater improvement in problem-solving skills than those who did not.